Three-component taxonomy of Abdul Alizada in Azerbaijan psychopedagogy - Султанова, Илхама (Pedagogy and Psychology, 2020)
The article examines the concept of Alizade’s three-component taxonomy, which is the psychological basis of the national educational program in Azerbaijan. It is noted that the taxonomy of learning goals has been studied by various scientists as an object of research since the 1930s, conceptual models have been created that reflect the structure of cognitive processes and intelligence. A.Alizade was the first to create a three-component taxonomy based on the principles of modern education theory. There are two variants of Alizade’s taxonomy. In the first version (1998), taxa are analyzed in the context of the Education –Development – Education trilogy with conceptual dimensions of modern education theory. In the second version (2007) of the trilogy the following: «Education – Development Culture». «Three-component taxonomy» by professor A.Alizade is the scientific and psychological basis of the document «Concept of general education (National Curriculum) in the Republic of Azerbaijan». Research conducted confirms the need for educational taxonomies to set the right educational goals so that students can formulate objectives correctly, select adequate assessment tools, and conduct accurate analysis based on learning In our opinion, in the current context of education reform in our country, there is a need for a broader study of the philosophical, psychological and pedagogical issues of the concept of taxonomy of learning objectives.